Magnetization transfer measurements in normal-appearing cerebral white matter in patients with chronic obstructive hydrocephalus - Hähnel, Stefan; Münkel, Kristin; Jansen, Olav; Heiland, Sabine; Reidel, Margot; Freund, Michael; Aschoff, Alfred; Sartor, Klaus (Journal of computer assisted tomography, 1999)
Purpose: The purpose of this work was to assess the presence of subtle changes in normal-appearing white matter on T2-weighted MR images in patients with chronic obstructive hydrocephalus using magnetization transfer (MT) measurements. - Method: In 12 patients with chronic obstructive hydrocephalus, MT ratios (MTRs) of normal-appearing rostral (PR) and caudal (PC) periventricular white matter, of the genu (CG) and the splenium (CS) of the corpus callosum, and of the thalamus (TH) were measured and compared with those of 16 healthy control subjects. - Results: We found a significantly lower MTR in chronic obstructive hydrocephalus than in the normal group for PR, PC, CG, and CS but not for TH. - Conclusion: Our study shows that MT measurements give additional information that cannot be gained by conventional SE MRI, suggesting that chronic obstructive hydrocephalus is associated with diffuse white matter damage that also affects normal-appearing cerebral white matter.
Gesehen am 11.03.2021